Chapter Movimento portuale, reti marittime e diversità dei mercati a Valenza nel XV secolo - Igual Luis, David (Atti delle «Settimane di Studi» e altri Convegni, 2019)
An analysis of Valencia's fifteenth-century port activity functional to the study of the city's diverse maritime networks and markets based on first-hand archive research mainly focusing on the second half of the fifteenth century. The text also takes into account an assortment of further late-fourteenth to early-sixteenth century data collected and analysed by other authors.